Being counted? Examining the prevalence of looked‐after disabled children and young people across the UK. Issue 1 (19th June 2015) - Hill, Louise; Baker, Claire; Kelly, Bernadette; Dowling, Sandra
Abstract: Since the 1970s, there has been growing academic interest in children and young people living in state care and, more recently, in the lives of disabled children. However, there has been little attention on the lives of disabled children who are looked after by the state. This paper compares and critiques what is known about the numbers of disabled children who are looked after in England, Northern Ireland, Scotland and Wales. We discuss the conceptual and methodological limitations of systematically collecting data on disabled children in state care across the UK. We argue that to ensure that the rights of disabled children in state care are identified, acknowledged and upheld, 'being counted' is a fundamental first step.